Decentralized secondary frequency restoration and power sharing control in islaned microgrid systems - Lian, Zhijie (2019)
In this paper, a totally decentralized control scheme is proposed to address the secondary frequency restoration and real power sharing problem in AC microgrid (MG) systems. Different from existing centralized or distributed control approaches, no communication among controllers is required with our method, which greatly eases the system implementation cost. It is theoretically proved that the designed decentralized leaky integral controllers can restore the frequency to its nominal value with bounded steady-state error, which can be arbitrarily small by choosing proper control parameters. In addition, the proposed controller can also adjust the real power sharing ratio according to different working conditions. An islanded AC MG test system consisting of 4 distributed generators (DGs) is built in MATLAB Simulink environment and the simulation results validate the effectiveness of proposed decentralized control approach.